Language Learning Strategy-Task Corollary: A Case of Jigsaw vs. Problem-solving Tasks (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This study aimed at investigating the relationship between language learning strategy use and performing jigsaw and problem-solving tasks. For this purpose, 53 students of a total 77 BA students majoring at ELT, English Literature, and English Translation were chosen through taking the Standardized Nelson English Proficiency Test. The homogeneous participants were randomly divided into two experimental groups: jigsaw and problem-solving. The jigsaw group practiced reading comprehension through jigsaw tasks while the problem-solving group did so through problem-solving tasks. Strategic behavior of each group was assessed through administrating the Strategy Inventory of Language Learning (SILL) prior to and after the treatment. The data obtained undergone three main statistical analyses: independent sample t-test, paired samples t-test and MANOVA. Between group comparison indicated that the two groups were not much different regarding the strategy use implying that task type does not much affect strategy use. However, within group comparisons revealed that, although the strategies as a unitary entity did not change as a result of the exposure to the task types, they showed changes in their use of various components of the strategies; metacognitive, social, and cognitive strategies were used most frequently by the members of both groups. Interestingly, the findings sustain the old but still attractive notion of Gestalt Psychology that the whole, is other than sum of the parts (Kurt Koffka).